2006
DOI: 10.1038/ni1421
|View full text |Cite
|
Sign up to set email alerts
|

Kinase MEKK1 is required for CD40-dependent activation of the kinases Jnk and p38, germinal center formation, B cell proliferation and antibody production

Abstract: Mice lacking activity of the kinase MEKK1 ('Map3k1(deltaKD)' mice) have defective activation of the kinase Jnk and increased production of T helper type 2 cytokines after T cell receptor ligation. Here we show that Map3k1(deltaKD) mice had defective germinal center formation and diminished production of antibodies recognizing thymus-dependent antigens. Those defects were B cell intrinsic, as MEKK1 was necessary for CD40-mediated activation of the kinases Jnk and p38 and transcription factor c-Jun, as well as f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(112 citation statements)
references
References 40 publications
3
106
0
3
Order By: Relevance
“…In addition to hypertrophy and cell survival, there is evidence showing the involvement of MEKK1-JNK in epithelial cell migration for reepithelialization of injured tissue, as observed with MEKK1 mutant mice with a deletion of the kinase domain (MEKK1 KD/KD ; Deng et al, 2006). In another study, Gallagher et al (2007) found that mice deficient in MEKK1 kinase activity have diminishing B-cell numbers. Specifically, B-cell proliferation is positively regulated by CD40-dependent mobilization of MEKK1-JNK/ p38 signal indicating MEKK1 activity contributes to the development of clonal populations of B cells.…”
Section: Mekk1 (Omim#*600982)mentioning
confidence: 96%
“…In addition to hypertrophy and cell survival, there is evidence showing the involvement of MEKK1-JNK in epithelial cell migration for reepithelialization of injured tissue, as observed with MEKK1 mutant mice with a deletion of the kinase domain (MEKK1 KD/KD ; Deng et al, 2006). In another study, Gallagher et al (2007) found that mice deficient in MEKK1 kinase activity have diminishing B-cell numbers. Specifically, B-cell proliferation is positively regulated by CD40-dependent mobilization of MEKK1-JNK/ p38 signal indicating MEKK1 activity contributes to the development of clonal populations of B cells.…”
Section: Mekk1 (Omim#*600982)mentioning
confidence: 96%
“…Similar patterns were observed for cyclin D2, c-Fos, c-Jun and p27 kip1 protein expression (Online Supplementary Figure S7B). Given the known requirement of the ERK/AP-1/cyclin D2 pathway for GC B-cell proliferation, 41,43 these results might explain the defective progression of …”
Section: Myc/igh+mentioning
confidence: 97%
“…Several studies have shown that MEKK1 is required for B and T cell activation (Zhang et al, 2003a;Labuda et al, 2006;Kim et al, 2007). MEKK1 is necessary for CD40-mediated activation of Jnk and p38 kinases, and it is an essential component of signaling cascades involved in thymus-dependent antigen-induced B cell proliferation and antibody production (Gallagher et al, 2007). The MEKK1 kinase domain has been shown to be important for IL4 and IL6 gene expression under Th2 conditions (Enzler et al, 2009).…”
Section: Gene Namementioning
confidence: 99%